Thermodynamic, structural, and mechanical properties of fluoropolymers from molecular dynamics simulation: Comparison of force fields. (21st September 2019) - Tamir, Erez; Sidess, Arieh; Srebnik, Simcha
Highlights: Prediction of thermomechanical properties of fluoropolymers is at its infancy. Atomistic force fields for fluoropolymers are parametrized for oligomers. Atomistic forcefields are tested for accuracy and transferability to longer chains. Large variability in predicted properties of different force fields are discussed. Abstract: Copolymers of vinylidene fluoride (VDF) and hexafluoropropylene (HFP) make up the largest volume of fluoroelastomers sales. Within this family, Viton A (VDF/HFP 60/40 wt%, 66% fluorine) is most important commercially. Determination of thermomechanical properties of such fluorinated polymers is still limited to experimentation or empirical models, while computational prediction of their physical properties is still at its infancy. Considerable efforts have been made to develop molecular force fields for the prediction of properties of various crystalline as well as amorphous fluorinated substances. These force fields were parametrized based on small molecules or oligomers, hence their transferability to longer and more complex (i.e. copolymer) chain architectures must be tested. In this work, thermodynamic, structural, and mechanical properties of the Viton A fluoroelastomer are evaluated using atomistic molecular dynamics (MD) simulations for several force fields and compared with available experimental data. Differences in molecular structure of the chains modeled by different force fields are shown to substantially influence thermodynamic and mechanical behavior. OPLS-derived force fields give rise to extended chains that are more mobile and result in softer material that lack in molecular structure. Other force fields rely on strong nonbonded interactions that interfere with chain dynamics and mechanics. PCFF is shown to most satisfactorily predict structural properties and thermal volumetric behavior around Tg, demonstrating relatively successful transferability to long linear polymer chains.